The rate and pattern of urea infusion into the rumen of wethers alters nitrogen balance and plasma ammonia - Recavarren, Mariana Ines (2014)
Changes in N balance, urinary excretion of purine derivative (PD), urea, creatinine and ammonia and plasma ammonia, glucose, urea, insulin and IGF-1 were examined in four wethers (37 ± 2.6 kg BW). The animals were fitted with permanent ruminal catheters, fed lucerne hay (9.4 MJ/day; 23 g N/day; 7 g soluble N/day, 6 equal meals/day) and treated with contrasting rates of urea infusion into the rumen: first, a continuous infusion (CT), at 3.2 mg urea-N/min for 10 days and then a discontinuous infusion (DT) at 156 mg urea-N/min for 4 min; in 6 daily doses with the meals for 7 days. N balance was calculated from pooled samples of faeces and urine. Jugular blood samples were collected before and 1.5 h after the morning meal (M1) on days CT10, DT2, DT4 and DT6. N retention decreased during DT (p = 0.01) due to a significant increase of N excretion in urine (4 g/day; p = 0.009) and faeces (1 g/day; p = 0.02). Dry matter (p < 0.001) and N digestibility in vivo (p = 0.01) decreased significantly during DT. Urinary urea and PD excretion were not altered by treatment. Significant linear (p = 0.004) and quadratic (p = 0.001) effects were observed for plasma ammonia in M1 (from 170 CT10 to 235 μm DT2 and returned to 120 μm DT6). No changes were observed in plasma glucose, urea, insulin and IGF-1. Results indicate that changes from CT to DT reduced N retention in sheep due to enhanced urinary N excretion, but it was not associated with changes in urinary urea or PD excretion; or plasma concentrations of insulin and IGF-1. As the dry matter (DM) an N digestibility could account a 0.23 of the decrease in N retention; the largest fraction of the reduction in N retention remained unexplained by the results.